2003
DOI: 10.1152/ajpgi.00093.2002
|View full text |Cite
|
Sign up to set email alerts
|

Local presentation of Steel factor increases expression of c-kit immunoreactive interstitial cells of Cajal in culture

Abstract: The binding of Steel factor (SF) to c-kit initiates a signaling pathway essential for development and maintenance of interstitial cells of Cajal (ICC). Soluble and membrane-bound isoforms of SF are expressed in the gastrointestinal tract, but the role for either isoform in supporting ICC development is unknown. The aim of this study was to determine the role of SF in supporting ICC in culture. ICC were cultured from dissociated mouse jejunum and grown with fibroblast cell lines that produced either soluble, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 38 publications
1
64
0
1
Order By: Relevance
“…Indeed, the only well-accepted regulator of ICC survival and development is stem cell factor (Bernex et al 1996;Ward et al 1999;Rich et al 2003), the ligand for the Kit tyrosine kinase receptor. Maeda et al (1992) reported previously that blockade of Kit on alternate days from Day 0 to 8 postpartum (p.p.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the only well-accepted regulator of ICC survival and development is stem cell factor (Bernex et al 1996;Ward et al 1999;Rich et al 2003), the ligand for the Kit tyrosine kinase receptor. Maeda et al (1992) reported previously that blockade of Kit on alternate days from Day 0 to 8 postpartum (p.p.)…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry ICC in primary cell culture were identified by immunofluorescence double-labeling of c-Kit and CD44, as previously described (Rich et al 2003). The culture medium was removed from the cover slips, and thereafter, all of the cells that were cultured with or without different concentrations of NaHS were fixed with acetone (4°C, 10 min), washed with PBS, incubated with 10% normal donkey serum (NDS), and 0.2% Triton-X-100 (Sigma, St. Louis, Missouri, USA) in 0.1 M PBS for 1 hour to minimize nonspecific antibody binding, and incubated with the rat monoclonal anti-c-Kit antibody ACK2 (1:100) (eBioscience, San Diego, California, USA) diluted in 5% NDS for 2 hours at 37°C.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…50 Briefly, Sl/Sl 4 mSCF248, murine stem cell factor-secreting fibroblasts (provided by Dr. David Williams, Indianapolis, IN) were plated on 22-mm plain glass coverslips at 4.5 ϫ 10 4 cells per coverslip in highglucose Dulbecco's modified Eagle medium containing 10% fetal bovine serum, 1% sodium pyruvate, and 1% antibiotic-antimycotic (all from Invitrogen). After 30 hours, the fibroblast cell division was arrested by irradiation at 16000 Gy.…”
Section: Mouse Icc and Murine Fibroblast Coculturesmentioning
confidence: 99%
“…50 Briefly, acetonefixed coverslips (4°C, 10 min) were washed with phosphate-buffered saline (PBS), incubated with 10% normal donkey serum (NDS, Jackson Immunoresearch Laboratories, West Grove, PA) and 0.2% Triton-X-100 (Sigma) in PBS for 1 hour to minimize nonspecific antibody binding and then incubated with primary antibody (1/150 in 5% NDS) overnight at 4°C. Next, the sections were rinsed in PBS and incubated in the dark for 1 hour at room temperature with donkey anti-rat IgG conjugated to CY3 (Jackson Immunoresearch Laboratories, 1/800 dilution in 2.5% NDS).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Moreover, MC themselves are able to synthesize, contain and release SCF (Zhang et al 1998, de Paulis et al 1999. Recent studies indicate that membranebound SCF stimulates activation of the c-kit receptor more effectively than soluble SCF (Linenberger et al 1995, Welker et al 1999, Rich et al 2003.…”
Section: Discussionmentioning
confidence: 99%